Identifying the proficiency level of primary English language teachers’ productive skills from Kurikulum Merdeka and CEFR - Pujianto, Dimas; Damayanti, Ika Lestari; Hamied, Fuad Abdul; Sari, Della Nuridah Kartika (citeus, 2023)
This study aims to identify the language proficiency level of primary English language teachers’ (PELTs) productive skills (speaking and writing) analyzed using the Common European Framework of References (CEFR) and Kurikulum Merdeka. As a foreign language in Indonesia, English language proficiency among PELTs is crucial to determine the success of the learning process in a classroom. Furthermore, PELTs should also possess adequate language proficiency to communicate effectively with students in any situation. However, several local context studies show the low language proficiency level possessed by PELTs. The low proficiency level was mostly gained through general English tests, for example TOEFL, which focuses on teachers’ receptive skills (listening and reading) and structure. A qualitative approach and case study research design were employed in this study. It was identified that the majority of teachers’ productive skills proficiency level is categorized into the B1/B2 level of CEFR. Additionally, the mixed level of proficiency among PELTs is still apparent which can create issues regarding primary-students’ language development and the standard of proficiency level that PELTs should be. Therefore, by involving subject teachers' communities and the government, a standard of language proficiency for PELTs should be developed.